Analysis of the Process of Cooperation Plan between Batu City and Fukushima City in the Agricultural Sector for the Period of 2016-2025 - Alkatiri, Sarah; Abdullah (Journal of Paradiplomacy and City Networks, 2025)
This study analyzed the process and challenges of the planned agricultural cooperation between Batu City (Indonesia) and Fukushima City (Japan) from 2016 to 2025. Using a qualitative descriptive method, the research drew on primary data from interviews with local government officials and institutional actors, supported by relevant documentation. The analysis was grounded in two frameworks: Aldecoa and Keating’s theory of paradiplomacy, emphasizing the role of subnational governments in international cooperation, and Indonesia’s Ministry of Home Affairs Regulation No. 25 of 2020, which sets the procedural standards for foreign cooperation at the regional level. The findings revealed that while initial steps were taken—such as bilateral visits and preliminary program design—the cooperation did not progress to formal implementation due to regulatory non-compliance, leadership discontinuity, and weak institutional coordination. Specifically, the absence of reporting to the central government, lack of an MoU, and inadequate bureaucratic integration hindered the realization of the agreement. Despite these challenges, opportunities remained for revitalizing the cooperation, particularly under new leadership that has expressed a willingness to re-engage. This study contributes to the growing discourse on paradiplomacy in Indonesia and offers practical insights into the governance and institutional conditions necessary for effective city-to-city collaboration in the agricultural sector.